Comparison Of Seismic Performance Of High Rise Rcc Building For Various Configurations Of Fluid Viscous Damper - Khatri, Abhinesh; Sah, Roshan Kumar; Lama, Sachin; Shrestha, Suyog; Ojha, Bimal (Journal of Advanced College of Engineering and Management, 2026)
The vulnerability of reinforced concrete (RC) buildings to earthquake forces specially in seismically active region like Nepal highlights the need for improved seismic performance through the use of energy dissipation devices. This study investigates the effectiveness of fluid viscous dampers in improving the seismic behavior of a multi-storey RC building by comparing different damper configurations. A G+12 reinforced concrete building located in Kathmandu (Seismic Zone V) was modeled and analyzed using ETABS v19 in accordance with the provisions of NBC 105:2025. Response spectrum analysis was performed to evaluate the seismic response of five different structural models: a building without dampers and four models with fluid viscous dampers arranged in different configurations, including alternate bay all-storey, corner bay all-storey, alternate bay alternate-storey, and corner bay alternate-storey arrangements. The seismic performance of the building models was evaluated in terms of time period, storey displacement, storey drift, and storey shear. The results indicate that the installation of fluid viscous dampers significantly reduces storey displacement by about 45% compared to the building without dampers. Among the studied configurations, the alternate bay alternate-storey damper configuration demonstrated the most effective reduction in displacement and drift, providing better control of structural response while using fewer dampers compared to the all-storey configurations. Although the inclusion of dampers slightly increases storey shear due to additional damping forces, the overall structural performance is significantly enhanced. The findings of this research may contribute to the adoption of supplemental damping systems for improving earthquake resilience of buildings in seismic regions like Kathmandu.